2021
DOI: 10.1186/s13071-020-04541-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral peritoneal immunity to Mesocestoides vogae metacestode infection in mice

Abstract: Background Here, Mesocestoides (M.) vogae infection in mice is proposed as a suitable experimental model for studying the immunity in the peritoneal cavity of mice. Methods To investigate the kinetics of immune parameters in M. vogae-infected mice, we detected, using flow cytometry, the expression of selected lymphoid and myeloid markers within the peritoneal cell population at day 0, 3, 6, 10, 14, 19, 25, 30 and 35 post-infection. Then, using ELIS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…They are also used in veterinary medicine. In the current study, we evaluated the impact of ABZ and DLE administration on the inflammatory responses and larval counts in the peritoneal cavity utilizing the M. vogae mouse model, where larvae asexually reproduce despite a robust immune response from the mouse hosts [ 26 , 28 ]. In our study, the highest reduction was observed after combined treatment with both drugs, suggesting that DLE, although being non-larvicidal in vitro (unpublished observations), enhanced the drug´s efficacy via the activation of antiparasitic immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also used in veterinary medicine. In the current study, we evaluated the impact of ABZ and DLE administration on the inflammatory responses and larval counts in the peritoneal cavity utilizing the M. vogae mouse model, where larvae asexually reproduce despite a robust immune response from the mouse hosts [ 26 , 28 ]. In our study, the highest reduction was observed after combined treatment with both drugs, suggesting that DLE, although being non-larvicidal in vitro (unpublished observations), enhanced the drug´s efficacy via the activation of antiparasitic immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that STAT1 gene expression in PECs was gradually downregulated while transcript levels for STAT3, STAT6, and IL-10 were markedly elevated within the course of M. vogae infection in mice [ 28 ]. The binding of IL-10 activates a cascade of molecules including the STAT3 factor required for the anti-inflammatory effects of IL-10 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of IP-administered DLE alone and as the adjuvant with albendazole were investigated during infection of mice with proliferating metacestodes of Mesocestoides vogae . DLE increased the larvicidal effect of albendazole on the parasites in the livers and the peritoneal cavities, stimulated the proliferation of T lymphocytes, and modified the serum cytokine profiles towards the balanced Th1/Th2 type ( Mačak Kubašková et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dialyzable leukocyte extract (DLE), available under the commercial name IMMODIN (ImunaPharm, Ltd. Slovakia) is the cell homogenate prepared from desintegrated blood leukocytes of healthy human donors. In our previous studies we have shown that this type of DLE administered as an adjuvant to ABZ enhanced the drug´s efficacy via stimulation of Th1 and attenuation of Th2/Treg biased immune responses in mice infected with model metacestodes of Mesocestoides vogae ( Mačak Kubašková et al ., 2018 ). DLEs of human and animal origin typically consist of various biologically active components, which include cyclic nucleotides, nicotinamide, purine bases, histamine, ascorbates, prostaglandins, serotonin, amino acids, proteins, etc.…”
Section: Introductionmentioning
confidence: 99%